Combining Meyer–Miller Hamiltonian with electronic structure methods for on-the-fly nonadiabatic dynamics simulations: implementation and application. Issue 31 (24th July 2019) - Tang, Diandong; Fang, Wei-Hai; Shen, Lin; Cui, Ganglong
Abstract : The MM/SQC method combined with electronic structure calculations at the level of OM2/MRCI and on-the-fly nonadiabatic dynamics simulations. Abstract : The semiclassical approaches such as the Meyer–Miller mapping Hamiltonian in conjunction with the symmetrical quasi-classical windowing (MM/SQC) method have been widely used to study nonadiabatic processes in photochemistry but still limited to model Hamiltonians. In this work we implemented the MM/SQC method combined with electronic structure calculations at the level of OM2/MRCI and the on-the-fly nonadiabatic dynamics simulations. The two-state-involved photoisomerization process of cis -azobenzene is employed as a realistic molecular system for validation. The MM/SQC method is able to reproduce the experimental results and provides an alternative to the conventional surface hopping simulations. The optimal windowing procedures such as the window functions and parameters in MM/SQC are suggested for future applications.